Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Anggaran Pada Dinas Kesehatan Kabupaten Jepara - Fatchur Rohman; Yudhi Dharmansyah (Accounting Study Program, Faculty of Economics and Business, 2019)
This study aims to examine the effect of planning documents, administrative records, human resource competencies, procurement documents, and money supply on budget absorption at the Jepara District Health Office. The research sample was 44 respondents who held positions in areas related to the budget, including Financial Administration Officers, Committee Making Officers, Technical Implementation Officers, Expenditure Treasurers, and implementing activities at the Jepara District Health Office. The results of the study using multiple linear regression showed that planning documents, administrative records, human resource competencies, and procurement documents had a significant influence on budget absorption. While the money supply does not affect the absorption of the budget.